Canadian VR technology will aid isolation effects on a simulated long duration space flight - McDonald, Bob (CBC Radio, 2021)
Bob McDonald's blog: The virtual reality experience was designed to simulate the 'overview effect' that sparks a sense of awe in astronauts when they look down at Earth from space
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage